GAMIFICATION IN TEACHING THEORETICAL LINGUISTIC DISCIPLINES - Mirzoyeva, Leila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Gamification in the learning process is a well-known and, at the same time, an entirely new teaching tool. Today, a number of gaming techniques can be attributed not only in the real classroom, but also in the virtual learning environment. In both cases, games have significant motivating potential. On the other hand, prospects for the modern world development require getting both theoretical knowledge and practical skills, and games provide all the opportunities for getting them.Traditional team games, as well as contests between individuals, are widely used in learning process at universities Moreover, there are various types of up-to-date platforms for creating and introducing online games such as Kahoot!, Quizlet, Plickers, Classcraft, etc. However, it should be noted that all the listed platforms and techniques are used primarily in teaching practical disciplines (e.g. Practical English) while for theoretical courses, traditional teaching methods and teacher-centered approaches continue to prevail. We believe that various techniques of gamification (both real and virtual) will increase the level of students’ motivation while studying theoretical courses. Thus, such disciplines as Research Techniques in Linguistics, is a very complicated course for the 3rd year BA students; so in order to motivate them, different games were introduced. In our research, we used a questionnaire aimed at finding out how the introduction of games enhances students’ motivation to study this discipline.Also, the experiment which lasted for 1 semester with the students whose major is "Foreign Philology", showed that the application of different games a) motivated students and activated their schemata; b) facilitate mastering complicated theoretical concepts; so gamification should be considered as an effective tool in teaching theoretical disciplines.